Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2147/clep.s28390
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and therapies for metastatic sarcoma

Abstract: Sarcomas are cancers arising from the mesenchymal layer that affect children, adolescents, young adults, and adults. Although most sarcomas are localized, many display a remarkable predilection for metastasis to the lungs, liver, bones, subcutaneous tissue, and lymph nodes. Additionally, many sarcoma patients presenting initially with localized disease may relapse at metastatic sites. While localized sarcomas can often be cured through surgery and often radiation, controversies exist over optimal management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 176 publications
0
53
0
1
Order By: Relevance
“…Prior to the emergence of effective chemotherapy, 2-year overall survival rates following surgical resection and/or radiotherapy were 15–20% (4,5). Further advances in therapeutic strategies for OS, including wide tumor excision, neoadjuvant and adjuvant chemotherapy, and radiotherapy, have resulted in significantly improved clinical outcomes and long-term survival rates (2,69). However, >30% of patients with OS survive for <5 years and succumb due to pulmonary metastases following diagnosis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the emergence of effective chemotherapy, 2-year overall survival rates following surgical resection and/or radiotherapy were 15–20% (4,5). Further advances in therapeutic strategies for OS, including wide tumor excision, neoadjuvant and adjuvant chemotherapy, and radiotherapy, have resulted in significantly improved clinical outcomes and long-term survival rates (2,69). However, >30% of patients with OS survive for <5 years and succumb due to pulmonary metastases following diagnosis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…They are broadly classified as either soft-tissue sarcomas (STSs), including more than 50 histologic subtypes, or bone neoplasms. Sarcomas represent 1% of all cancers in adults, 10% in children, and 8% in adolescents and young adults 1. Despite their rarity, sarcomas contribute to a substantial loss of years of life compared to other cancers, because of the many children, adolescents, and young adults diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have been associated with exposure to radiation, chemotherapeutic agents, viral infections, occupational factors, and hereditary syndromes 1. Their prognosis is variable according to the histologic type, but often poor and presumably related to hematogenous spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing efforts have illustrated the key role of p53 mutation in this malignancy and investigated the structural variations that characterize this disease (12). Metastatic osteosarcoma continues to be a significant challenge and the most recent clinical trial demonstrated feasibility of adding zoledronic acid to the chemotherapeutic backbone in this setting (13, 14). Efforts to better incorporate the young adult population into clinical trials and discern outcomes in this group compared to the younger patients are underway as well (1517).…”
Section: Introductionmentioning
confidence: 99%